Comprehensive Lower Extremities Joints Range of Motion Profile in Futsal Players - Cejudo, Antonio; Ruiz-Pérez, Iñaki; Hernández-Sánchez, Sergio; De Ste Croix, Mark; Sainz de Baranda, Pilar; Ayala, Francisco (Frontiers in Psychology, 2021)
The purposes of this study were to describe the lower extremity joints range of motion (ROM) profile using a comprehensive approach in futsal players and to examine potential player position (goalkeepers vs. outfield players), level of play (first [top] division vs. second division), number of playing years, sex (males vs. females) and bilateral (dominant limb vs non-dominant limb) differences. A total of 72 male and 67 female elite futsal players from 11 clubs were measured of passive hip (flexion with knee flexed [HFKF] and extended [HFKE], extension [HE], abduction [HA], external [HER] and internal [HIR] rotation), knee (flexion [KF]) and ankle (dorsiflexion with knee flexed [ADFKF] and extended [ADFKE]) ROMs. Bayesian inferences exploring differences between player position, level of play, sex and limb were made. A Bayesian correlation analysis was conducted to explore the influence of playing years on joints ROMs. The results showed no significant player position or level of play related differences in any average ROM score. However, statistically significant sex-related differences were documented whereby female players reported higher hip and knee joints ROM average values than their male counterparts. Especially relevant were the proportions of males (72%) and players from teams engaged in the second division (61%) displaying limited HFKE ROMs. Likewise, around 35% of all players showed restricted ADFKF ROMs. In addition, approximately 21, 18, 22 and 25% of the futsal players were identified as having bilateral asymmetries (≥8°) for HA, HIR, HER and KF ROMs, respectively. Finally, Bayesian correlation analysis did not report any significant association between years of playing futsal and ROM measures (all r values <0.34). The findings of this study reinforce the necessity of prescribing exercises aimed at improving HFKE and ADFKF ROM values routinely in everyday futsal training. Furthermore, as some bilateral deficits were observed, unilateral training should be considered where appropriate.